1982
DOI: 10.1177/002188638201800105
|View full text |Cite
|
Sign up to set email alerts
|

Racial Exclusion in Juries

Abstract: This study examines the norms of jury selection, determines which norms are most important in qualifying individuals for jury service, and discusses how the interpretation and application of these norms influence the racial composition of juries as blacks progress from the jury list to the jury panel and to the jury box. The data come from a questionnaire survey of 1,551 legal personnel-district clerks, jury commissioners, state attorneys, defense attorneys, and judges-who are most directly associated with sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…However, there is some reason to believe that exclusion at stage of compilation of juror lists was significant relative to discrimination at later stages in reducing the representation of nonwhites on juries relative to their population share. A 1972 survey of jury commissioners, district clerks, state attorneys, defense attorneys and judges in 325 counties in the South with large African American populations found that self-reported race shares at different stages (jury list, jury box, jury) indicate that a large fraction of the disparity between population shares and jury service race shares materialized at the stage of the compilation of the jury list (Benokraitis, 1982). 9…”
Section: Jury Selection Proceduresmentioning
confidence: 99%
“…However, there is some reason to believe that exclusion at stage of compilation of juror lists was significant relative to discrimination at later stages in reducing the representation of nonwhites on juries relative to their population share. A 1972 survey of jury commissioners, district clerks, state attorneys, defense attorneys and judges in 325 counties in the South with large African American populations found that self-reported race shares at different stages (jury list, jury box, jury) indicate that a large fraction of the disparity between population shares and jury service race shares materialized at the stage of the compilation of the jury list (Benokraitis, 1982). 9…”
Section: Jury Selection Proceduresmentioning
confidence: 99%
“…However, there is some reason to believe that exclusion at stage of compilation of juror lists was significant relative to discrimination at later stages in reducing the representation of nonwhites on juries relative to their population share. A 1972 survey of jury commissioners, district clerks, state attorneys, defense attorneys and judges in 325 counties in the South with large African American populations found that self-reported race shares at different stages (jury list, jury box, jury) indicate that a large fraction of the disparity between population shares and jury service race shares materialized at the stage of the compilation of the jury list (Benokraitis, 1982). 5…”
Section: Jury Selection Proceduresmentioning
confidence: 99%
“…Benokraitis (1982) found that in such states, jury commissioners and district clerks reported using personal knowledge to select potential jurors, or consulting acquaintances to eliminate a significant number of jurors from the lists based on reports of "character" and "intelligence".…”
mentioning
confidence: 99%
“…Some have claimed that all stages of jury selection processes, including these middle stages, introduce racial biases (Alker, Hosticka, & Mitchell, 1976;Benokraitis, 1982;Fukurai et al, 1991aFukurai et al, , 1991b. The empirical work, however, has not consistently supported that point.…”
Section: Middle Stages Of Juror Selectionmentioning
confidence: 99%